Alternative dispute resolution methods in turkish law and Mediation (Journal of actual problems of jurisprudence, 2022)
One of the priority directions of legal reform at the present stage of development is the improvement of the system of application of alternative means of dispute resolution, designed to effectively and promptly ensure the resolution of disputes arising in civil law and related spheres of society in the process of building a democratic rule of law. To resolve the issues of the dispute, the subjects, the participants must come to a compromise in order to satisfy the requirements for each other. This issue is relevant for all countries of the world, which, to a greater or lesser extent, carry out transformations of civil justice systems for various periods of time. In this regard, it is obvious that today, both in developed and developing countries, significant experience has been formed and accumulated in reforming this area, which can form the basis of similar transformations in Turkey and significantly contribute to facilitating ongoing reforms by avoiding other people's mistakes and using mechanisms to obtain positive results.Keywords: reform, disputes, civil law, subject, mediation.